PWiseGen: Generating test cases for pairwise testing using genetic algorithms - Flores, P.; Yoonsik Cheon (2011 IEEE International Conference on Computer Science and Automation Engineering, 2011)
Pairwise testing is a combinatorial testing technique that tests all possible pairs of input values. Although, finding a smallest set of test cases for pairwise testing is NP-complete, pairwise testing is regarded as a reasonable cost-benefit compromise among combinatorial testing methods. In this paper we formulate the problem of finding a pairwise test set as a search problem and apply a genetic algorithm to solve it. We also describe an open-source tool called PWiseGen for generating pairwise test sets. PWiseGen produces competitive results compared with existing pairwise testing tools. Besides, it provides a framework and a research platform for generating pairwise test sets using genetic algorithms; it is configurable, extensible, and reusable.